Clash of Cultures: Muslims and Christians in the Ethnosizing Process - Amelie F. Constant; Liliya Gataullina; Klaus F. Zimmermann; Laura Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
The paper explores the evolution of ethnic identities of two important and distinct immigrant religious groups. Using data from Germany, a large European country with many immigrants, we study the adaptation processes of Muslims and Christians. Individual data on language, culture, societal interactions, history of migration and ethnic self-identification are used to compose linear measures of the process of cultural adaptation. Two-dimensional variants measure integration, assimilation, separation and marginalization. Christians adapt more easily to the German society than Muslims. Immigrants with schooling in the home country and with older age at entry as well as female Muslims remain stronger attached to the country of origin. Female Muslims integrate and assimilate less and separate more than Muslim men, while there is no difference between male and female Christians. Christians who were young at entry are best integrated or assimilated, exhibiting lower separation and marginalization in the later years, while for Muslims a similar pattern is observed only for assimilation and separation. Christian immigrants with college or higher education in the home country integrate well, but Muslims do not. For both religious groups, school education in the home country leads to slower assimilation and causes more separation than no education at home. While school education has no impact on integration efforts for Muslim, it affects similar attempts of Christians negatively.
Keywords: J15; Z12; F22; Z10; J16; 330; Ethnicity; ethnic identity; religion; migrant assimilation; migrant integration; ethnic exclusion; Einwanderung; Ethnische Gruppe; Soziale Integration; Christentum; Islam; Bildungsniveau; Deutschland